Pengembangan Potensi Green Economy dan Masyarakat Bebas Stunting KKN USK Desa Jamur Ujung, Kecamatan Wih Pesam, Kabupaten Bener Meriah - Satriyo, Purwana; Rianjuanda (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2023)
Bucket cultivation is a farming method in which plants are grown and maintained in bucket-shaped containers or similar containers. This method is suitable for limited spaces or difficult environments, such as small yards or balconies. In this cultivation process, fertile soil is mixed with the right composition to provide sufficient nutrition for the plants. After that, the seeds or plant seeds are planted in a bucket and given water regularly. Watering must be regulated carefully, and fertilization also needs to be paid attention to so that the plants grow fertile and healthy. Meanwhile, Gutel Kupi is a popular traditional cake, especially in the Bener Meriah, Gayo, Aceh areas. Making Gutel Kupi starts by mixing wheat flour, granulated sugar, ground coffee (Gayo Coffee if possible), margarine or butter, eggs, baking powder, vanilla and a little salt in a bowl. Mix all ingredients until smooth and form an elastic dough. After the dough has rested, shape it into small balls and fry in hot oil until golden. Thus, cultivating in a bucket is a farming technique in a limited container, while Gutel Kupi is a traditional Acehnese cake made from a mixture of wheat flour, sugar and coffee which is then fried. Both enrich cultivation and culinary practices in the context of local culture and wisdom. The combination of cultivation in buckets that produce nutritious plants and consumption of traditional foods such as Gutel Kupi which are rich in nutrients can play an important role in efforts to prevent stunting. It is also important to ensure that a balanced diet and adequate nutrition are observed in order to achieve optimal growth and development in children.